Situational similarity and personality predict behavioral consistency.[article]. - Sherman, Ryne A.
A new method for assessing situations is employed to examine the association between situational similarity, personality, and behavioral consistency across ecologically representative contexts. On 4 occasions across 4 weeks, 202 undergraduate participants (105 women, 97 men) wrote descriptions of a situation they had experienced the previous day. In addition, they rated its psychological features using the recently developed Riverside Situational Q-Sort(RSQ)Version 2.0 (Wagerman & Funder, 2009) and their behavior using the Riverside behavioral Q_Sort(RBQ)Version3.0 (Funder, Furr< & Colvin, 2000; Furr, Wagerman, & Funder, 2010). Independent judges also rated tha situations using the RSQ, on the basis of the participants' written descriptions. Results indicated (a)participants ratings of their behavior were impressively consistent across the 4 situations; (b)the four situations experienced by a single participant tended to be described more similarly to each other to situations experienced by different participants; (c)situational similarity, especially from the individual's own point of view, strongly predicted behavioral consistency; and (d)personality characteristics predicted behavioral consistency even after controlling for situational similarity. Relatively consistent persons described themeselves as ethically consistent, conservative, calm and relaxed, and low on neuroticism. These results imply that behavioral consistency in daily life stems from multiple sources, including situation selection and the distinctive influence of personality, and further suggest that tools for situational assessment such as the RSQ can have utility.